Roadmap on soft robotics: multifunctionality, adaptability and growth without borders. Issue 3 (1st September 2022) - Mazzolai, Barbara; Mondini, Alessio; Del Dottore, Emanuela; Margheri, Laura; Carpi, Federico; Suzumori, Koichi; Cianchetti, Matteo; Speck, Thomas; Smoukov, Stoyan K; Burgert, Ingo; Keplinger, Tobias; Siqueira, Gilberto De Freitas; et al.
Abstract: Soft robotics aims at creating systems with improved performance of movement and adaptability in unknown, challenging, environments and with higher level of safety during interactions with humans. This Roadmap on Soft Robotics covers selected aspects for the design of soft robots significantly linked to the area of multifunctional materials, as these are considered a fundamental component in the design of soft robots for an improvement of their peculiar abilities, such as morphing, adaptivity and growth. The roadmap includes different approaches for components and systems design, bioinspired materials, methodologies for building soft robots, strategies for the implementation and control of their functionalities and behavior, and examples of soft-bodied systems showing abilities across different environments. For each covered topic, the author(s) describe the current status and research directions, current and future challenges, and perspective advances in science and technology to meet the challenges.